Sertifikasi Halal untuk UMKM: Menavigasi Persepsi dan Implementasi Melalui Kacamata Maslahah Mursalah - Muhammad Rafiuddin; Daffa Aulia Ramadhan; Siti Nur Azizah (Muttaqien Publishing, Lembaga Penelitian dan Pengabdian kepada Mayarakat (P3M) STAI DR. KH.EZ. Muttaqien Purwakarta, 2024)
Halal certification has become a must to be implemented by MSME business actors in Indonesia. Moreover, economic activities in Indonesia have been dominated by the MSMEs industry. This study will explain the perception and application of halal certification by MSME business actors in Indonesia in terms of the principle of Maslahah Mursalah. The research method used in this study is a literature review focusing on journal articles published between 2018 and 2022. A total of 15 journal articles were reviewed. Research utilizing the literature study method shows that most business actors already know the importance of halal certification for the sustainability of their business, whether it can increase consumer confidence or increase their sales turnover. However, the results of the application implementation still need to be improved compared to the number of MSMEs in Indonesia. There are still many MSMEs business actors who still need to be halal certified. For this reason, the principle of maslahah has not been appropriately implemented, seeing that the level of halal certification is still minimal.